The University and the Global Knowledge Society - Frank, David John; Meyer, John W. (Book collections on Project MUSE., 2020)
"This book examines the core changes in the nature, status, and significance of the university over the last century. Having grown in numbers, reach, and scope, the university has seen sweeping expansion and has become central in a contemporary global society built on liberal and neoliberal institutions. David Frank and John Meyer begin by describing the university's expansion, focusing especially on global diffusion. They then examine the transformation of university knowledge, illustrating the ways in which standardized and scientific knowledge now reaches into more sectors of everyday life. This leads them to discuss the porous interface between the university and society. They suggest that there are now essentially no social problems that the university should not responsibly address. The result is a society dependent on credentials and cultural content provided by the university, and in the final chapter of the book, the authors reflect on what it means to exist in this "knowledge society""--